2022
DOI: 10.18517/ijaseit.12.3.14724
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Model for Sentiment Analysis of COVID-19 Tweets

Abstract: COVID-19 pandemic presents unprecedented challenges and enormously affects different aspects of individuals' lives worldwide. The implementation of different prevention measures, the economic and social disruption, and the significant rise in the mortality rate greatly affect the peoples' spectrum of emotions. Sentiment analysis, an important branch of artificial intelligence, uses machine learning techniques to understand public perspectives and gain more insights into how they think and feel. During the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Compared to other models in the study, the XGB Classifier had the third highest accuracy score. Additionally, one previous study by Aljabri et al ( 2022 ) reported a high accuracy of 90% for the XGB Classifier, further highlighting its effectiveness. The XGB Classifier's ability to capture complex patterns and interactions in the data likely contributed to its successful performance.…”
Section: Discussion Of Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Compared to other models in the study, the XGB Classifier had the third highest accuracy score. Additionally, one previous study by Aljabri et al ( 2022 ) reported a high accuracy of 90% for the XGB Classifier, further highlighting its effectiveness. The XGB Classifier's ability to capture complex patterns and interactions in the data likely contributed to its successful performance.…”
Section: Discussion Of Resultsmentioning
confidence: 75%
“…The SVM model, although not consistently outperforming the other models across previous studies, still demonstrates competitive accuracy scores. For instance, in the study by Aljabri et al (2022), SVM achieved an accuracy of 88%. Similarly, in the current study, SVM/SVC performed well with an accuracy score of 96.2%.…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%
“…XGBoost [ 68 ] is considered one of the most superior and advanced methods among all ML algorithms, which uses the principle of boosting. This method also implements an ensemble technique as an RF algorithm.…”
Section: Machine Learning Methodsmentioning
confidence: 99%
“…However, there is a lack of research concerning COVID-19 tweet datasets, especially in the context of the Nepali language. Examination of sentiment in the English and Nepali language using machine and deep learning has been the subject to numerous studies [1], [4], [5], [7], [9], [11], [12] .…”
Section: Related Workmentioning
confidence: 99%
“…In the past, due to COVID-19, social media posts, especially tweets, increased rapidly. Much research [2][3][4] has been conducted in the area of sentiment analysis related to COVID-19 tweets for languages such as English and other widely spoken languages. Still, there has been a relative lack of research on the sentiment analysis of tweets connected to the COVID-19 in Nepali language.…”
Section: Introductionmentioning
confidence: 99%